Interactive effects of temperature and drought on cassava growth and toxicity: implications for food security?. (4th August 2016) - Brown, Alicia L.; Cavagnaro, Timothy R.; Gleadow, Ros; Miller, Rebecca E.
Abstract: Cassava is an important dietary component for over 1 billion people, and its ability to yield under drought has led to it being promoted as an important crop for food security under climate change. Despite its known photosynthetic plasticity in response to temperature, little is known about how temperature affects plant toxicity or about interactions between temperature and drought, which is important because cassava tissues contain high levels of toxic cyanogenic glucosides, a major health and food safety concern. In a controlled glasshouse experiment, plants were grown at 2 daytime temperatures (23 °C and 34 °C), and either well‐watered or subject to a 1 month drought prior to harvest at 6 months. The objective was to determine the separate and interactive effects of temperature and drought on growth and toxicity. Both temperature and drought affected cassava physiology and chemistry. While temperature alone drove differences in plant height and above‐ground biomass, drought and temperature × drought interactions most affected tuber yield, as well as foliar and tuber chemistry, including C : N, nitrogen and cyanide potential (CNp; total cyanide released from cyanogenic glucosides). Conditions that most stimulated growth and yield (well‐watered × high temperature) effected a reduction in tuber toxicity, whereas drought inhibited growth and yield, and was associated with increased foliar and tuber toxicity. The magnitude of drought effects on tuber yield and toxicity were greater at high temperature; thus, increases in tuber CNp were not merely a consequence of reduced tuber biomass. Findings confirm that cassava is adaptable to forecast temperature increases, particularly in areas of adequate or increasing rainfall; however, in regions forecast for increased incidence of drought, the effects of drought on both food quality (tuber toxicity) and yield are a greater threat to future food security and indicate an increasing necessity for processing of cassava to reduce toxicity.